Cognitive flexibility as Mediator the Effect of Loneliness on Celebrity worship in Early adult Korean Wave Fans in Indonesia - Krismana, Muhamad Gilang; Rahman, Puspa Rahayu Utami; Dimala, Cempaka Putrie (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2023)
Celebrity worship is an obsessive-addictive disorder where a person becomes involved in every detail of their idol's activities (Maltby et. al, 2005). This study aims to determine cognitive flexibility as a mediator of the effect of loneliness on celebrity worship in early adult korean wave fans in Indonesia. The research method uses quantitative and causality approaches. The measuring instruments used are the Cognitive Flexibility Inventory (CFI) scale by Dennis & Vander Wal (2010, the UCLA Loneliness Scale (ULS-20) scale by Russel (1996), and the Celebrity Attitude Scale (CAS) scale by Maltby et al (2004). The population of this study was early adult korean wave fans in Indonesia, with a sample of 496 participants including 113 men and 383 women. Mediation analysis was used using the SEM mediation analysis feature of the JASP software version 16. The results showed the value of the direct effect of the loneliness variable on celebrity worship, with a p value of 0.001 <0.05, which indicates that the loneliness variable has a significant effect on celebrity worship. On the other hand, the value of the indirect effect between the variable loneliness on celebrity worship and cognitive flexibility as a mediator was obtained, with a p value of 0.001 <0.05, which shows that cognitive flexibility functions as a mediator of the effect of loneliness on celebrity worship. which means that the cognitive flexibility variable can reduce celebrity worship caused by the loneliness variable.Celebrity worship merupakan gangguan obsesif-adiktif dimana seseorang menjadi terlibat pada setiap detail aktivitas idolanya (Maltby et. al, 2005). Penelitian ini bertujuan untuk mengetahui cognitive flexibility sebagai mediator pengaruh loneliness terhadap celebrity worship pada dewasa awal penggemar korean wave di Indonesia. Metode penelitian menggunakan pendekatan kuantitatif dan kausalitas. Alat ukur yang digunakan adalah skala Cognitive Flexibility Inventory (CFI) oleh Dennis & Vander Wal (2010, skala UCLA Loneliness Scale (ULS-20) oleh Russel (1996), dan skala Celebrity Attitude Scale (CAS) oleh Maltby et al (2004). Populasi penelitian ini merupakan dewasa awal penggemar korean wave di Indonesia, dengan sampel sebanyak 496 partisipan diantaranya 113 laki-laki dan 383 perempuan. Analisis mediasi digunakan menggunakan fitur SEM mediation analysis dari perangkat lunak JASP versi 16. Analisis mediasi digunakan menggunakan fitur SEM mediation analysis dari perangkat lunak JASP versi 16. Hasil penelitian menunjukkan nilai pengaruh langsung variabel loneliness terhadap celebrity worship. Di sisi lain, nilai pengaruh tidak langsung antara variabel loneliness terhadap celebrity worship dan cognitive flexibility sebagai mediator diperoleh, dengan nilai p 0,001 < 0,05, yang menunjukkan bahwa cognitive flexibility berfungsi sebagai mediator pengaruh loneliness terhadap celebrity worship. yang berarti variabel cognitive flexibility dapat penurunan celebrity worship yang disebabkan oleh variabel loneliness.